A Bayesian approach to spatial filtering and diffuse power estimation for joint dereverberation and noise reduction - Chakrabarty, Soumitro; Thiergart, Oliver; Habets, Emanuël (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2015)
Keywords: dereverberation; Bayesian beamforming; microphone array processing

A Data-Driven Approach to Audio Decorrelation - Anemüller, Carlotta; Thiergart, Oliver; Habets, Emanuël (IEEE Signal Processing Letters, 2022)
The degree of correlation between two audio signals entering the ears is known to have a significant impact on the spatial perception of a sound image. Audio signal decorrelation is therefore a widely used tool in various applications within the field of spatial audio processing. This paper explores for the first time the use of a data-driven approach for audio decorrelation. We propose a convolutional neural network architecture that is trained with the help of a state-of-the-art reference decorrelator. The proposed approach is evaluated using music and applause signals by means of objective evaluations as well as through a listening test. The proposed approach can serve as a proof of concept to address common limitations of existing decorrelation techniques in future work, which include introduction of temporal smearing and coloration artifacts and the production of a limited number of mutually uncorrelated output signals.
CRIS-Team WoS Importer:2023-01-13

A low complexity weighted least squares narrowband DOA estimator for arbitrary array geometries - Thiergart, Oliver; Huang, Weilong; Habets, Emanuël (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2016)

A method to analyze the spatial response of informed spatial filters - Chakrabarty, Soumitro; Thiergart, Oliver; Habets, Emanuël (Proc. of the ITG Conference on Speech Communication, 2016)

An acoustical zoom based on informed spatial filtering - Thiergart, Oliver; Kowalczyk, Konrad; Habets, Emanuël (Proc. Intl. Workshop Acoust. Echo Noise Control (IWAENC), 2014)
Keywords: microphone arrays; Spatial sound acquisition; Optimum beamforming

An informed LCMV filter based on multiple instantaneous direction-of-arrival estimates - Thiergart, Oliver; Habets, Emanuël (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2013)
Keywords: microphone array processing; diffuse-to-noise ratio estimation; optimal beamforming

An informed MMSE filter based on multiple instantaneous direction-of-arrival estimates - Thiergart, Oliver; Taseska, Maja; Habets, Emanuël (Proc. European Signal Processing Conf. (EUSIPCO), 2013)
Keywords: dereverberation; optimal beamforming; microphone array processing

An informed parametric spatial filter based on instantaneous direction-of-arrival estimates - Thiergart, Oliver; Taseska, Maja; Habets, Emanuël (IEEE/ACM Transactions on Audio, Speech and Language Processing, 2014)
Keywords: Dereverberation; Microphone array processing; Interference reduction; Optimal beamforming

Automatic spatial gain control for an informed spatial filter - Braun, S.; Thiergart, Oliver; Habets, Emanuël (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2014)
Keywords: informed spatial filtering; automatic gain control; microphone arrays

BINAURAL RENDERING OF HETEROGENEOUS SOUND SOURCES WITH EXTENT - Anemüller, Carlotta; Thiergart, Oliver; Habets, Emanuël (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2024)
In spatial audio rendering applications, it is often desired to render sound sources with a certain spatial extent in a realistic way. While existing methods mainly consider rendering of homogeneously extended sound sources (i.e., with constant radiation characteristics over the extent), rendering of heterogeneously extended sound sources (i.e., with position-dependent radiation characteristics) has barely been discussed in the literature. In this paper, we propose an approach for binaural rendering of heterogeneously extended sound sources. Input to the algorithm is a two-channel signal, which provides information about the position-dependent radiation characteristics of the sound source. Based on a model for an extended sound source with position-dependent energy and spectral content, the target covariance matrix of the binaural output signal is determined. Using a previously proposed optimal mixing approach, a binaural output signal with the desired properties is obtained, ensuring that the spatial characteristics encoded in the two-channel input signal are preserved. The proposed approach is evaluated both objectively and subjectively by comparing it to two homogeneous extent-rendering baselines as well as to simple point source reproduction.
CRIS-Team Scopus Importer:2024-06-14
Keywords: binaural rendering; spatial extent

Coherence-based diffuseness estimation in the spherical harmonic domain - Jarrett, Daniel Phillip; Thiergart, Oliver; Habets, Emanuël; Naylor, Patrick (Proc. IEEE Convention of Electrical and Electronics Engineers in Israel (IEEEI), 2012)

Combining linear spatial filtering and non-linear parametric processing for high-quality spatial sound capturing - Thiergart, Oliver; Milano, Guendalina; Habets, Emanuël (Proc. IEEEIntl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2019)

Diffuseness estimation with high temporal resolution via spatial coherence between virtual first-order microphones - Thiergart, Oliver; Del Galdo, G.; Habets, Emanuël (Proc. IEEE Workshop on Applications of Signal Processing to Audio and Acoustics, 2011)
Keywords: Microphone arrays; Spatial audio; Parameter Estimation; Spatial coherence

Evaluation and Comparison of Late Reverberation Power Spectral Density Estimators - Braun, Sebastian; Kuklasinski, A.; Schwartz, O.; Thiergart, Oliver; Habets, Emanuël; Dolco, Simon; Gannot, Sharon; Jensen, J. (IEEE/ACM Transactions on Audio, Speech and Language Processing, 2018)
Keywords: Dereverberation; diffuse sound; array processing; power spectral density estimation; speech enhancement

Extracting reverberant sounds using multiple microphones - Thiergart, Oliver; Habets, Emanuël (Proc. of the International Conference on Spatial Audio, 2014)

Extracting reverberant sound using a linearly constrained minimum variance spatial filter - Thiergart, Oliver; Habets, Emanuël (IEEE Signal Processing Letters, 2014)
Keywords: Array signal processing; Source separation; Microphone arrays; Spatial filters

Generating virtual microphone signals using geometrical information gathered by distributed arrays - Del Gado, G.; Thiergart, Oliver; Weller, T.; Habets, Emanuël (Proc. of the Joint Workshop on Hands-free Speech Communication and Microphone Arrays, 2011)
Keywords: Audio recording; Sound localization; Parameter estimation; Spatial sound

Geometry-based spatial sound acquisition using distributed microphone arrays - Thiergart, Oliver; Del Galdo, Giovanni; Taseska, Maja; Habets, Emanuël (IEEE Transactions on Audio Speech and Language Processing, 2013)
Keywords: position estimation; microphone arrays; Spatial sound acquisition; signal-to-diffuse ratio

Interactive Teleconferencing Combining Spacial Audio Object Coding and DirAC Technology - Herre, Jürgen; Falch, Cornelia; Mahne, Dirk; Del Galdo, Giovanni; Kallinger, Markus; Thiergart, Oliver (Journal of the AES, 2011)
herre_books_journals

Interactive Teleconferencing Combining Spatial Audio Object Coding and DirAC Technology - Herre, Jürgen; Falch, Cornelia; Mahne, Dirk; Del Galdo, Giovanni; Kallinger, Markus; Thiergart, Oliver (128nd AES Convention, 2010)
The importance of telecommunication continues to grow in our everyday lives. An ambitious goal for developers is to provide a most natural way of audio communication by giving users the impression of being located next to each other. MPEG Spatial Audio Object Coding (SAOC) is a technology for coding, transmitting, and interactively reproducing spatial sound scenes on any conventional multi-loudspeaker setup (e.g. ITU 5.1). This paper describes how Directional Audio Coding (DirAC) can be used as a recording front-end for SAOC based teleconference systems to capture acoustic scenes and to extract the individual objects (talkers). By introducing a novel DirAC to SAOC parameter transcoder, a highly efficient way of combining both technologies is presented which enables interactive, object-based spatial teleconferencing.
herre_papers_spatial_audio_coding_and_3d_audio_coding

Interactive teleconferencing combining Spatial Audio Object Coding and DirAC technology - Herre, Jürgen; Falch, Cornelia; Mahne, Dirk; Del Galdo, Giovanni; Kallinger, Markus; Thiergart, Oliver (Journal of the Audio Engineering Society, 2011)
The importance of telecommunication continues to grow in our daily lives. An ambitious goal for developers is to provide the most natural means of audio communication by giving users the perception of being located next to each other. MPEG Spatial Audio Object Coding (SAOC) is a technology for coding, transmitting, and interactively reproducing spatial sound scenes on any conventional multi-loudspeaker setup (e.g., ITU 5.1). This paper describes how Directional Audio Coding (DirAC) can be used as a recording front end for SAOC-based teleconferencing systems, capturing acoustic scenes and extracting the individual objects (talkers). By introducing a novel DirAC to SAOC parameter transcoder, a highly efficient way of combining both technologies is presented which enables interactive, object-based spatial teleconferencing.
herre_books_journals

Multi-channel sound acquisition using a multi-wave sound field model - Thiergart, Oliver; Habets, Emanuël (Wiley-IEEE Press, 2017)
Keywords: Direction of arrival; Parametric sound field model; Multi-channel filters; Spatial sound reproduction; Second-order statistics; State-of-the-art

On the spatial coherence in mixed sound fields and its application to signal-to-diffuse ratio estimation - Thiergart, Oliver; Del Galdo, Giovanni; Habets, Emanuël (Journal of the Acoustical Society of America, 2012)

Parametric sound acquisition using a multi-wave signal model and spatial filters - Thiergart, Oliver; Habets, Emanuël (Time-frequency Domain Parametric Spatial Audio, 2017)

Parametric spatial sound processing: A flexible and efficient solution to sound scene acquisition, modification, and reproduction - Kowalczyk, Konrad; Thiergart, Oliver; Taseska, Maja; Del Galdo, Giovanni; Pulkki, Ville; Habets, Emanuël (IEEE Signal Processing Magazine, 2015)

Power-based signal-to-diffuse ratio estimation using noisy directional microphones - Thiergart, Oliver; Tobias, Ascherl; Habets, Emanuël (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2014)
Keywords: directional microphones; array signal processing; signal-to-diffuse ratio

Robust 3D sound capturing with planar microphone arrays using directional audio coding - Thiergart, Oliver; Milano, Guendalina; Tobias, Ascherl; Habets, Emanuël (Proc. Audio Eng. Soc. Convention, 2017)

Robust direction-of-arrival estimation of two simultaneous plane waves from a B-format signal - Thiergart, Oliver; Habets, Emanuël (Proc. IEEE Convention of Electrical and Electronics Engineers in Israel (IEEEI), 2012)

Signal-to-reverberant ratio estimation based on the complex spatial coherence between omnidirectional microphones - Thiergart, Oliver; Del Galdo, G.; Habets, Emanuël (Proc. IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2012)
Keywords: Array signal processing; spatial coherence; signal-to-reverberation ratio

Six-degrees-of-freedom binaural audio reproduction of first-order ambisonics with distance information - Plinge, Axel; Schlecht, Sebastian; Thiergart, Oliver; Robotham, Thomas; Rummukainen, Olli; Habets, Emanuël (Proc. of the AES International Conference on Audio for Virtual and Augmented Reality, 2018)

Sound acquisition in noisy and reverberant environments using virtual microphones - Kowalczyk, Konrad; Thiergart, Oliver; Craciun, Alexandra; Habets, Emanuël (Proc. IEEE Workshop on Applications of Signal Processing to Audio and Acoustics, 2013)
Keywords: spatial filtering; microphone array processing; Wiener filtering; spatial sound recording

Sound field model violations in parametric spatial sound processing - Thiergart, Oliver; Habets, Emanuël (Proc. Intl. Workshop Acoust. Echo Noise Control (IWAENC), 2012)
Keywords: Spatial audio coding; Parametric spatial audio processing; W-disjoint orthogonality